Work-related violence: a conceptual proposal - Oliveira, Roberval Passos de; Nunes, Mônica de Oliveira (Saúde e Sociedade, 2008)
The increase of violence situations in the work environment is becoming an important Public Health problem, with impacts on workers' dignity and quality of life. In this perspective, the present article aims to propose the concept of work-related violence, as a reference for future studies in the field of Workers' Health starting from a discussion of the violence phenomenon and its work-related facet. This is a conceptual synthesis article, in which we have tried to look at the issue of violence and its interfaces with the concept of power, in order to build a definition able of embracing the diversity and complexity of the relationship between work and violence, and that is comprehensive enough as well as proving sufficiently comprehensive to incorporate the wealth of accumulated discussions in the field, without losing the possibility of being operative. We argue that the proposition of a work-related violence concept might avoid misunderstandings caused by using terms such as work violence and violence at work, as well as provide a better device to produce knowledge able to ground more accurate diagnostics about the Brazilian worker's condition and, consequently, substantiate the formulation of policies to fight violence and to promote citizenship.